2021
DOI: 10.3389/fcell.2021.650772
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Notch, Hedgehog, and Wnt Signaling Pathways in the Resistance of Tumors to Anticancer Therapies

Abstract: Resistance to therapy is the major hurdle in the current cancer management. Cancer cells often rewire their cellular process to alternate mechanisms to resist the deleterious effect mounted by different therapeutic approaches. The major signaling pathways involved in the developmental process, such as Notch, Hedgehog, and Wnt, play a vital role in development, tumorigenesis, and also in the resistance to the various anticancer therapies. Understanding how cancer utilizes these developmental pathways in acquiri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
58
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 107 publications
(75 citation statements)
references
References 223 publications
0
58
0
Order By: Relevance
“…We and others have demonstrated that aberrant Wnt/β-catenin signaling plays an important role in mediating resistance to different treatment modalities, including CRT [ 23 , 24 , 25 , 26 ]. To assess the influence of Wnt/β-catenin signaling in esophageal cancer cells, we first determined the expression levels of relevant Wnt-related proteins such as Axin2, active β-catenin (ABC), total β-catenin (TBC), and the Wnt-transcription factor TCF7L2 by Western blot analysis ( Figure 1 A).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We and others have demonstrated that aberrant Wnt/β-catenin signaling plays an important role in mediating resistance to different treatment modalities, including CRT [ 23 , 24 , 25 , 26 ]. To assess the influence of Wnt/β-catenin signaling in esophageal cancer cells, we first determined the expression levels of relevant Wnt-related proteins such as Axin2, active β-catenin (ABC), total β-catenin (TBC), and the Wnt-transcription factor TCF7L2 by Western blot analysis ( Figure 1 A).…”
Section: Resultsmentioning
confidence: 99%
“…Although these reports underpin the relevance of Wnt/β-catenin signaling for radioresistance, the underlying mechanisms are still not fully understood. Wnt/β-catenin signaling triggers numerous cellular and molecular mechanisms presumably involved in drug efflux, DNA damage repair, inhibition of apoptosis, regulation of the cell cycle, cellular survival, reactive oxygen species (ROS), induction of epithelial to mesenchymal transition (EMT), and modification of the tumor microenvironment (TME) [ 25 , 26 , 57 ], which all can be connected to treatment resistance.…”
Section: Discussionmentioning
confidence: 99%
“… 73 They are generally non-toxic, more readily available, and less costly than synthetic drugs, preventing several diseases in healthy individuals. Recent studies have also identified several potent inhibitors of the Wnt/β-catenin and hedgehog pathways, including curcumin, 74 resveratrol, epigallocatechin-3-gallate (EGCG), lycopene, and retinoids. 74 - 76 Analysis of these plant components revealed several unique inhibitors of the Wnt/β-catenin and hedgehog signaling pathways.…”
Section: Myoinositol and Folic Acid Role In Embryogenesismentioning
confidence: 99%
“…Furthermore, GSCs are considered to have enhanced capacity for DSB repair, with not only NHEJ [23] but also error-free HR contributing to resistance [24,25]. In addition, a number of survival pathways are frequently upregulated in GBM, including the PI3K/AKT pathway, which facilitates repair and may be antiapoptotic (reviewed in [26]), as well as the Notch, Hedgehog (Hh), and Wnt pathways that are associated with stemcell properties and therapy resistance (reviewed in [27]). The PI3K/AKT pathway is activated by Receptor Tyrosine Kinases (RTK), e.g., EGFR, frequently amplified and upregulated or mutated to produce a constitutive active variant GFRvIII present in approximately 30% of GBM.…”
Section: Gbm Heterogeneity and Gsc-related Therapy Resistancementioning
confidence: 99%